Construção e validação de uma cartilha de orientação sobre o tratamento quimioterápico - Pereira, Cláudia Regina (2014)
The development of educational guidance materials to patients undergoing chemotherapy aims to improve the quality of care since it is understood that when properly instructed on how to deal with the treatment they undergo increases the adhesion the information make the safer and contributes to the success of the treatment The aim of the study was to construct and validate a primer guidance on chemotherapy This is a methodological research which followed the following steps to develop and validate manuals for health education: project submission to the ethics committee bibliographic and production of an educational manual validation of material built For the construction of the booklet we performed a bibliographic survey of the following databases: SciELO LILACS Cochrane and PubMed using the keywords " cancer " " chemotherapy " " antineoplastic " " drug toxicity " and " care nursing " covering the period 2003-2013 synthesis of 19 articles selected guided guidance on the main side effects of chemotherapy ( nausea vomiting diarrhea mouth ulcers hair loss low immunity skin reactions and other ) and nursing care for these patients After choosing the content we sought to produce a rich educational material color to unwind and encourage reading the images have been carefully selected with the help of a professional graphic designer seeking at all times conform to the guidelines literature idealized characteristics of the instrument The construction of the booklet occurred from November 2013 to January 2014 Then the primer was validated by nine justices on the technical aspects all with extensive experience in the area of cancer and chemotherapy Data analysis was performed descriptively The rating assigned by judges to the items was mostly Totally appropriate and suitable The major considerations were made by the judges on Replacement technical expressions by terms that can be understood by the target audience and correction confusing guidelines The changes were intended to avoid complexity in the content of the booklet It is believed that the primer can contribute to the improvement of information to this population mitigating the effects of ignorance of the disease and its treatment fostering dialogue answering questions and facilitating educational practice nurses.